CURRENT STATUS OF CESAREAN SECTION FOR FIRST CHILD AT HA DONG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinical and sub-clinical characteristics and indications for primary cesarean section among nulliparous women at Ha Dong General Hospital from 1/7/2024 to 30/6/2025.Subject and methods: A cross-sectional study was conducted on 1,167 nulliparous women who underwent cesarean section at Ha Dong General Hospital between July 1, 2024, and June 30, 2025. Medical records were systematically reviewed to collect relevant data.Results: The mean maternal age was 28.6 ± 5.2 years, and the mean gestational age was 38.8 ± 1.4 weeks. Emergency cesarean sections accounted for 72.6% of all cases. Common sub-clinical findings included anemia, oligohydramnios, and abnormal placental localization. Indications for cesarean section were predominantly due to fetal causes (67.4%), followed by abnormal labor (13.1%), maternal causes (7.9%), placental or umbilical cord factors (6.8%), and social reasons (4.8%). Notably, fetal distress was identified as the most frequent individual indication.Conclusion: Primary cesarean sections at Ha Dong General Hospital were most common among young, full-term nulliparous women, with a high prevalence of emergency procedures. Many cases exhibited sub-clinical abnormalities related to pregnancy-associated pathologies. Social reasons remained a significant factor, highlighting the critical role of obstetric counseling and the need to optimize surgical indications to reduce unnecessary procedures.
Keywords: Nulliparous cesarean section, clinical characteristics, fetal distress, social reasons.